Three-dimensional scanning transmission electron microscopy of dislocation loops in tungsten. (October 2018) - Hasanzadeh, S.; Schäublin, R.; Décamps, B.; Rousson, V.; Autissier, E.; Barthe, M.F.; Hébert, C.
Highlights: STEM imaging at 200 kV was successfully applied to investigate the 3D spatial distribution and the Burgers vector of dislocation loops in tungsten ion irradiated at room temperature and 700 °C. A new approach was developed to reconstruct the 3D location of the dislocation loops from the STEM data, yielding original data. Reliable STEM data was derived in tungsten foils of up to 0.5 μm in thickness. It appears that the dislocation loops spatial distribution is broader than the simulated ion induced damage profile, indicating that they are highly mobile, even at room temperature. Abstract: Scanning transmission electron microscopy (STEM) imaging using diffraction contrast is a powerful technique to assess crystal defects. In this work it is used to assess the spatial distribution of radiation induced defect in tungsten. In effect, its irradiation leads to the formation of nanometric dislocation loops that under certain conditions may form intriguing 3-D rafts. In this study, we have irradiated thin tungsten samples in situ in a TEM with 1.2 MeV W ions to 0.017 dpa at room temperature (RT) and at 700 °C. Besides the Burgers vector analysis, the number density and size of the dislocation loops with their spatial arrangement were quantitatively characterized by stereo imaging in STEM mode. Most of the loops have a Burgers vector ½ a0 〈111〉, with some a0 〈100〉 at room temperature. Loops are located mainly in the simulated damage profile but there is also a significant portion in deeper regions of the sample, indicating that loops in W diffuse easily, even at RT. At 700 °C, loops form elongated rafts that contain dislocation segments having a Burgers vector ½ a0 〈111〉. The rafts are narrow and reside on { 111 } planes; they are elongated along 〈110〉 directions, which correspond, when combined to the rafts' Burgers vector, to the lines of edge dislocations. Compared to conventional TEM, 3-D analysis in STEM appears thus as a powerful technique for quantitative analyses of defects in tungsten, as it allows reducing the background diffraction contrast and reaching thicker areas of the electron transparent foil, here 0.5 μm of tungsten at 200 kV.